Tooth Size Discrepancies among Different Malocclusions in a Bangladeshi Orthodontic population (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Objectives: To identify the possible sex differences in anterior, posterior, and overall tooth size ratios and to evaluate whether any differences exist in tooth size ratios and distribution of subjects with clinically significant tooth size discrepancies among Angle class I, class II, & class III malocclusion groups in Bangladeshi Orthodontic population. Materials and Methods: Each malocclusion group comprised 40 subjects (20 males and 20 females).The mesiodistal width from first molar to first molar were measured on each pretreatment cast to the nearest 0.01mm using digital calipers, and the anterior, posterior and overall ratios were calculated. Students t-test, Wilcoxon nonparametric test, analysis of variance, and x2-test were performed for statistical analysis. Results: No statistically significant differences in anterior, posterior, or overall ratios were found among the malocclusion groups. No significant sex differences were found in anterior, posterior, or overall ratio in any group, Significant anterior and overall tooth size discrepancies outside 2 SD from the Bolton's means were found in 31% and11.6% of all malocclusion subjects respectively. Conclusion: Bolton's values can be used with confidence for the Bangladeshi orthodontic population. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16158 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 8-17